Literature Review: Sleep Quality Relationship with Depression Postpartum Symptoms - Annisa Qotrunnajah; Erna Herawati; S Sulistyani; Sri Wahyu Basuki (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: Postpartum depression is the most common psychiatric problem after giving birth which can last up to 1 year or even 2 years after giving birth. In addition to the mother, postpartum depression can also occur in the father. Symptoms of postpartum depression include an appetite disorder, anxiety, feeling worthless, depressed mood, suicidal thoughts and can affect the health of children's development. Postpartum women reported that during this period sleep disturbances often occur. Sleep disorder is vulnerable in postpartum and pregnancy and can cause disturbed mood so that in this situation there is a relationship between sleep quality and symptoms of postpartum depression. Objective: To determine the relationship between sleep quality and symptoms of postpartum depression. Methods: This study uses a literature review design by collecting research articles through various databases such as Google Scholar, PubMed and Science Direct. Results: There were 1068 articles found, then the researchers screened according to the restriction criteria, so that 15 articles were found to be reviewed. The fourteen research articles showed that there was a relationship between poor sleep quality and symptoms of postpartum depression. However, 2 of the 14 articles stated that postpartum depression symptoms had a relationship with postnatal sleep quality but not with prenatal sleep quality. Later, one article stated that there was no relationship between both of this. Conclusion: Sleep quality has a relationship with postpartum depression symptoms. In this case, poor sleep quality in pregnancy before and after delivery can worsen and predict postpartum depression symptoms, especially at 3 months and 6 months postpartum.